ÓXIDOS DE FERRO OBTIDOS A PARTIR DE DESCARTES DE AÇO APLICADOS NA ADSORÇÃO DO CORANTE VERMELHO CONGO - Borth, Ketlyn Wolfart (2020)
Iron oxides can be synthetized from acid digestion of ferrous compounds, as steel. These oxides may be applied as adsorbents to remove harmful substances from water used in the textile process and, therefore, creating a cycle for controlling pollutants using materials with pollutant origin. The iron oxides were synthetized from the acid digestion of steel waste (razor blades and bottle caps), followed by the alcaline coprecipitation or gelation with citric pectin. The oxides were characterized by X-ray fluorescence (XRF), X-ray diffractometry (XRD), X-ray absorption near edge structure (XANES), vibrational spectroscopy (FTIR and Raman), thermogravimetric analysis (TG/DTG), electronic spectroscopy (UV-Vis), scanning electron microscopy (SEM), nanoparticles tracking analysis (NTA) and zeta potential (). The samples were identified as iron oxides, in different crystalline phases due to the method and the starting reactants used in the synthesis. In the initial tests, for application as Congo red dye adsorbent, the oxides named LCNH and TCNH presented the highest efficiency in the set of produced samples. Thus, LCNH TCNH were chosen for the adsorption process studies and for the textural characterization by Brunauer, Emmentt, Teller (B.E.T.) method. The oxides presented adsorption capacity (qmax) of 418.4 mg.g-1 to LCNH and 104.2 mg.g-1 to TCNH, at room temperature, following the Langmuir model of adsorption mechanism. The values of qmax and LCNH were higher than those found in the literature. Furthermore, the particles present magnetic properties from the iron oxides phases, which facilitates their removal from the system by magnetic attraction after the application. The adsorbents were characterized post-adsorption through the same initial techniques; thus, the compounds generated could be correlated to the adsorptive capacity of each oxide. Then, a cyclic voltammetry study was performed, and the voltammogram profile suggested a destination of the oxide-dye waste as pseudocapacitor, completing the sustainability cycle.